U.S. : (McGraw-Hill, 2009)
U*S: A Narrative History tells the story of us, the American people, with all the visually engaging, personally involving material that your students demand. From a trusted author team, this innovative text provides instructors who normally choose either a big or brief book with scholarly, succinct, and conventionally organized core content; a highly readable and unified narrative that is continental in scope; and a magazine format that engages students and helps them connect with the nation's past.